3
$\begingroup$

Let $$2\sin{11^{\circ}}\sin{71^{\circ}}\sin{(x^{\circ}+30^{\circ})}=\sin{2013^{\circ}}\sin{210^{\circ}}$$ where $90^{\circ}<x<180^{\circ}$.

My idea: $$2\sin{11^{\circ}}\sin{71^{\circ}}\sin{(x^{\circ}+30^{\circ})}=\sin{33^{\circ}}\sin{30^{\circ}}$$ and $$\Big[\cos{(71^{\circ}-11^{\circ})}-\cos{(71^{\circ}+11^{\circ})}\Big]\sin{(x^{\circ}+30^{\circ})}=\dfrac{1}{2}\sin{33^{\circ}}$$ and $$(1-2\sin{8^{\circ}})\sin{(x^{\circ}+30^{\circ})}=\sin{33^{\circ}}$$

I used Wolfram|Alpha to find $x=19$ or $101$.

My question: we can't use Wolfram|Alpha. How to find this $x$? Thank you.

$\endgroup$
  • 7
    $\begingroup$ Instead of using ^{0} for degrees sign, use ^{\circ}, it looks nicer. $\endgroup$ – Kaish Apr 30 '13 at 9:25
2
$\begingroup$

$$2\sin (x+30^\circ)\sin 11^\circ\sin 71^\circ=\sin 33^\circ\sin 30^\circ=\frac12(3\sin 11^\circ-4\sin^311^\circ)$$ applying $\sin3y=3\sin y -4\sin^3y$

$$\implies 4\sin (x+30^\circ)\sin 71^\circ=3-4\sin^211^\circ=3-2(1-\cos22^\circ)$$ as $\sin11^\circ\ne0$

$$\implies 2\{\cos(x-41^\circ)-\cos(x+101^\circ)\}=2\left(\cos22^\circ+\frac12\right)$$

One way to solve is to put

$(1)\cos(x-41^\circ)=\cos22^\circ,\cos(x+101^\circ)=-\frac12$

or $(2)\cos(x+101^\circ)=-\cos22^\circ=\cos(180-22)^\circ$ as $\cos(\pi-y)=-\cos y$ $=\cos158^\circ,\cos(x-41^\circ)=\frac12$

$(1)\implies x-41^\circ=360^\circ n\pm22^\circ$ where $n$ is any integer.

Taking $'+'$ sign, $x=360^\circ n+41^\circ+22^\circ=360^\circ n+63^\circ$ $\implies \cos(x+101^\circ)=\cos(360^\circ n+63^\circ+101^\circ)=\cos164^\circ \ne-\frac12$ $\implies x\ne360^\circ n+63^\circ$

Taking $'-'$ sign, $x=360^\circ n+41^\circ-22^\circ=360^\circ n+19^\circ$ $\implies \cos(x+101^\circ)=\cos(360^\circ n+19^\circ+101^\circ)=\cos120^\circ=-\frac12$ $\implies x=360^\circ n+19^\circ$ is a solution

$(2)\implies x+101^\circ=360^\circ m\pm158^\circ$ where $m$ is any integer

Taking $'+'$ sign, $x=360^\circ m+158^\circ-101^\circ=360^\circ m+57^\circ$ $\implies \cos(x-41^\circ)=\cos(360^\circ n+57^\circ-41^\circ)=\cos16^\circ \ne\frac12$ $\implies x\ne360^\circ m+57^\circ$

Taking $'-'$ sign, $x=360^\circ m-158^\circ-101^\circ=360^\circ m-259^\circ$ $\implies \cos(x-41^\circ)=\cos(360^\circ m-259^\circ-41^\circ)=\cos(-300^\circ)=\cos(360^\circ-60^\circ)=\cos60^\circ=\frac12$ $\implies x=360^\circ m-259^\circ$ is another solution

$\endgroup$
2
$\begingroup$

You've over complicated the whole thing wayyy too much. Don't forget, apart from $\sin(x + 30^{\circ})$, the rest are just constants and so treat them like any other number. Therefore you can just do the whole thing simply and like normal:

$$2\sin(11^{\circ})\sin(71^{\circ})\sin{(x+30^{\circ})}=\sin(2013^{\circ})\sin(210^{\circ})$$

$$ = 2\sin({11^{\circ}})\sin({71^{\circ}})\sin{(x^{\circ}+30^{\circ})}=\sin({33^{\circ}})\sin({30^{\circ}})$$

as they're all multiplied, divide through by the $2\sin(11)\sin(71)$ to get

$$\sin(x + 30^{\circ}) = \frac{\sin(33^{\circ})\sin(30^{\circ})}{2\sin(11^{\circ})\sin(71^{\circ})}.$$

Then $\arcsin$ both sides to get

$$x + 30^{\circ} = \sin^{-1} \left(\frac{\sin(33^{\circ})\sin(30^{\circ})}{2\sin(11^{\circ})\sin(71^{\circ})} \right) = 49^{\circ}.$$

Subtracting $30^{\circ}$ then gives you $x = 19^{\circ}$ and as you want it in the interval $90^{\circ} < x <180^{\circ}$, you simply do $90^{\circ} + 19^{\circ} = 109^{\circ}$.

$\endgroup$
  • $\begingroup$ oh,I have solution, I have forget,$\sin{(3x)}=4\sin{x}\sin{(60+x)}\sin{(60-x)}$, $\endgroup$ – math110 Apr 30 '13 at 9:27
  • 5
    $\begingroup$ How do you get $\sin^{-1}$ of that not obvious expression? $\endgroup$ – Ma Ming Apr 30 '13 at 9:41
  • $\begingroup$ @math110, Putting $x=11^\circ$ in your identity, $\sin(x+30^\circ)$ in the question will be $\sin(60^\circ-11^\circ)\implies x+30^\circ=49^\circ$ or $180^\circ-49^\circ$ as $\sin(180^\circ-y)=\sin y$ So, $x+30^\circ=49^\circ$ or $131^\circ$ $\endgroup$ – lab bhattacharjee Apr 30 '13 at 16:19
  • 1
    $\begingroup$ @Kaish : I upvoted your answer because someone had downvoted it but I liked your simple approach. However, you didn't explain why $\sin^{-1}(stuff) = 49^\circ$. Also, you claimed that $\sin(x + 30^\circ) = stuff$ implies $x + 30^\circ = \sin^{-1}stuff$, and we know that the inverse trig functions don't always work that nicely. $\endgroup$ – Stefan Smith Apr 30 '13 at 22:31
  • $\begingroup$ I genuinely thought, when OP said they used Wolfram, they meant they put the whole thing into Wolfram and it gave them a value for $x$. Not the fact that they meant they couldn't use any kind of calculator and so you simply just type in $sin^{-1} (stuff)$ into your calculator and it gives you the answer. $\endgroup$ – Kaish May 1 '13 at 10:12
0
$\begingroup$

$$2\sin 11^\circ*\sin 71^\circ*\sin (x+30)^\circ=\sin 2013^\circ*\sin 210^\circ$$

$$2\sin 71^\circ*\sin 11^\circ*\sin (x+30)^\circ=\sin 213^\circ*-\sin 30^\circ$$

$$2\sin 71^\circ*\sin 11^\circ*\sin (x+30)^\circ=-\sin 30^\circ*(\sin 213^\circ-\sin 71^\circ+\sin 71^\circ)$$

$$2\sin 71^\circ*\sin 11^\circ*\sin (x+30)^\circ=-\sin 30^\circ*(2\cos 142^\circ*\sin 71^\circ+2\cos 60^\circ*\sin 71^\circ)$$

$$2\sin 71^\circ*\sin 11^\circ*\sin (x+30)^\circ=-\sin 30^\circ*2sin 71^\circ*(\cos 142^\circ+\cos 60^\circ)$$

$$2\sin 71^\circ*\sin 11^\circ*\sin (x+30)^\circ=-\sin 71^\circ*(\cos 142^\circ+\cos 60^\circ)$$

$$2\sin 11^\circ*\sin (x+30)^\circ=(\cos 142^\circ+cos 60^\circ)$$

$$-2\cos 101^\circ*\sin (x+30)^\circ=-2\cos 101^\circ*cos 41^\circ$$

$$\sin (x+30)^\circ=\cos 41^\circ$$

$$\sin (x+30)^\circ=\sin 49^\circ$$

For $$(x+30)^\circ=49^\circ$$ or $$x^\circ=19^\circ$$

Also $$(x+30)^\circ=131^\circ$$ or $$x^\circ=101^\circ$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.